PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERBASIS MASALAH PADA MATERI FLUIDA STATIS DI SMK PGRI PONTIANAK - Emadi, Elisabeth Liseta; Djudin, Tomo; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to develop a problem-based static fluid learning module. This type of research was research and development (R&D) using the Borg & Gall model. The problem-based static fluid learning module consists of a cover, preface, table of contents, introduction, content, and conclusions. The results of the data analysis showed that the problem-based physics learning module in terms of content worthiness was 81.11%, presentation was 83.33%, language was 81% and graphics was 82.22% which included in the very high eligibility criteria. Students' responses in the initial field test were 81.49% (very high) and in the main field test amounted to 77.49% (high).Â Keywords: Development, Problem-Based Learning Module, Static Fluid